Influence of non-uniform mean flow on acoustic scattering from complex geometries. (15th February 2018) - Cheng, Long; Du, Lin; Wang, Xiaoyu; Wu, Long; Jing, Xiaodong; Sun, Xiaofeng
Highlights: An immersed boundary method is presented for sound scattering in non-uniform flow. Convergence analysis is performed for the method in a real viscous mean flow. The core wake region is proved to be of vital importance for sound directivity. Abstract: An immersed boundary computational model is presented to study the influence of non-uniform mean flow on acoustic scattering from complex geometries. It is firstly demonstrated from two benchmark problems that an absorbing treatment for the interior of solid domain in the developed immersed boundary method is not necessary. Then, simulations for acoustic scattering both from a circular cylinder and multiple bodies with different mean flow models are performed. It is found that the existence of a core wake region in a background mean flow model plays a significant role in accurately predicting acoustic directivity. When a sound source is in the core wake region, the background mean flow model has an obvious influence on the predicted acoustic directivity whether for a simple circular cylinder or multiple bodies; when the sound source is away from the core wake region, consistent results for different background mean flow models in most directions are obtained. However, about a maximum 8 dB discrepancy in the "front arm" direction of a circular cylinder and about a maximum 4.8 dB discrepancy in the downstream direction for the multi-element airfoil are caused respectively for the parallel and viscous mean flow models.